Additive Manufacturing of WC-Co Specimens with Internal Channels - Sykora, Jindrich; Sedlmajer, Michael; Schubert, Tim; Merkel, Markus; Kroft, Lubos; Kucerova, Ludmila; Rehor, Jan (Materials (Basel, Switzerland), 2023)
Most material removal in modern manufacturing is currently performed using tools with indexable inserts. Additive manufacturing allows for the creation of new, experimental insert shapes and, more importantly, internal structures, such as channels for coolant. This study deals with developing a process for efficiently manufacturing WC-Co specimens with internal coolant channels with a focus on obtaining a suitable microstructure and surface finish, especially inside the channels. The first part of this study covers the development of process parameters to achieve a microstructure without cracks and with minimal porosity. The next stage focuses solely on improving the surface quality of the parts. Special attention is given to the internal channels, where true surface area and surface quality are evaluated, as these characteristics greatly influence coolant flow. To conclude, WC-Co specimens were successfully manufactured and a microstructure with low porosity and no cracks was achieved and an effective parameter set was found. We have developed a process that produces parts with a surface roughness comparable to those of standard SLS manufacturing of steel parts, while still providing a high-quality internal microstructure. The most suitable parameter set resulted in a profile surface roughness of Ra 4 μm and Rz 31 μm and areal surface roughness of Sa 7 µm and Sz 125 µm.
Keywords: tungsten carbide; additive manufacturing; 3D printing; efficient cooling; indexable insert; preheating